Pengaruh Penggunaan Laboratorium Virtual Berbasis Web Terhadap Kemampuan Pemecahan Masalah Fisika Peserta Didik Pada Materi Gelombang Bunyi - Nurhasanah, Nurhasanah; Sutrio, Sutrio; Makhrus, Muh.; Susilawati, Susilawati (Universitas Hamzanwadi, 2023)
This research aims to determine the effect of using a web-based virtual laboratory on students' physics problem solving abilities on Sound Waves material. The type of research used was quasi-experimental with a Pretest-Posttest Nonequivalen Control Group Design research design. The population in this study were all class XI students at SMAN 6 Mataram. The research sample was obtained using the Purposive Sampling technique, namely XI MIPA 2 with a total of 15 students as the experimental class and class XI MIPA 3 with a total of 15 students as the control class. The sample in this study was only 15 students because the data that will be taken and used as samples are only students who took part in both activities, namely pre-test and post-test, and the population in this study is approximately 100, so the number of samples that can be taken is at least less than 50% of the population size. The test instrument used is in the form of questions describing problem solving abilities. Before the problem solving ability test instrument is given, a trial of the instrument is first carried out, namely testing validity, reliability, level of difficulty and differentiability. The results of the analysis show that the average score for the physics problem solving ability of students taught using a web-based virtual laboratory is 68.60 and the average score for students taught without using a web-based virtual laboratory is 52.67. The results of hypothesis testing using the t-test obtained a calculated of 3.92. Because the obtained is greater than the value, then is accepted and is rejected. These results show the influence of using a web-based virtual laboratory on students' physics problem solving abilities in class XI sound wave material at SMAN 6 Mataram.